If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 6y = 96 Solving 2x + 6y = 96 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6y' to each side of the equation. 2x + 6y + -6y = 96 + -6y Combine like terms: 6y + -6y = 0 2x + 0 = 96 + -6y 2x = 96 + -6y Divide each side by '2'. x = 48 + -3y Simplifying x = 48 + -3y
| y=6x^5+12x^3+6x^2-6x^3+7 | | 4(2t+1)=2(6t+5) | | 4(2t+1)=2(26t+5) | | 25x-4-19x=2(3x-4)+4 | | (8+9i)= | | 4(x+y)-2(x-9)+4= | | 0.07x=2000 | | -4/5=8/1x | | 3x/5+7y/4 | | 5/4(3x-1/2)-2/3=7/3 | | 3/4(3x-1/2)-7/3=5/3 | | ((v+5)/(v-3))=((v+7)/(v-5)+1) | | 7(8x-5)+12x= | | 2X^2+X=.44 | | e^5-3x=510 | | (3/8)/40=9/y | | 3+1/4*1-4/5 | | F=G*m*M/r^2 | | x+2*x+2=4 | | 8cos^2x=2 | | (3+1/4)(1-4/5) | | 5x^2+3x-.5=0 | | 49a^2-4=0 | | x^2-5x+6-0=0 | | H=5/3(a+2b) | | ln(x)=ln(x+6)-ln(3) | | 14-15+19=x-5 | | 14-15+19=33-5 | | 13a=13 | | ax-3c=5b | | 8x-4=5x+s | | 1/4k=4 |